Pembelajaran Bahasa Arab dengan Menggunakan E-Learning Berbasis Moodle - Aliyah, Siti Alfi; Hidayanti, Primasti Nur Yusrin (Study Program of Arabic Language Teaching, 2022)
This study examines the use of Moodle-Based E-Learning in Arabic Learning. The purpose of this study is to define and explain how Moodle-based e-learning can be used in learning Arabic. An analytical descriptive strategy based on a literature review was used as a research method. According to research findings, many students feel bored during the Arabic learning process, so it is necessary to make interesting and interactive media. One of the interesting uses of learning media in supporting education today is Moodle-based e-learning because Moodle has a number of unique and interesting features in supporting the learning process. Therefore, the use of moodle-based e-learning is very suitable for use in learning Arabic, given that currently the world of education cannot be separated from technology and internet networks, besides that there are many educational institutions that have been facilitated by infrastructure in utilizing existing technology.